Pengaruh Faktor Persepsi dan Sikap Terhadap Minat Masyarakat Sungai Binjai Menjadi Peserta BPJS-K Mandiri Dalam Perspektif Ekonomi Syariah - Rona Afriliani; Isamuddin .; Hendri Firmansyah; Yasirul Amri; M. Yunus (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
Interest refers to an internal drive within an individual that arises from a desire to choose a product, based on personal experience, a tendency to consume, or the intention to own the product. This interest does not emerge suddenly but is influenced by various factors, including perception and attitude, which play a crucial role in shaping a person's attraction toward a product. This study aims to examine the extent to which perception and attitude influence the interest of the community in Sungai Binjai to become independent BPJS (National Health Insurance) participants. The research employs a quantitative approach, with data analysis including validity and reliability tests, as well as hypothesis testing using t-test, F-test, and coefficient of determination (R²). The data analysis technique used is multiple linear regression. The results indicate that, based on the t-test, the perception variable (X1) does not have a significant effect on the community's interest in becoming independent BPJS participants. In contrast, the attitude variable (X2) shows a significant effect. The F-test result reveals a significance value of 0.008, which is lower than the 0.05 threshold, indicating that both perception and attitude simultaneously influence interest. However, the contribution of these two variables to interest is only 8.20%, while the remaining 91.80% is influenced by other factors not examined in this study.